External and internal morphometry of the four-toed Hedgehog (Atelerix albiventris Wagner, 1841) in Ibadan, Nigeria (2018)
Body size and measurements are important determinant of fitness in m any species. The four-toed hedgehog (Atelerix aibiventris) is the m ost preferred pet species of the hedgehogs and has been found in Africa to be eaten as bush m eat and hunted for fertility charms. This puts the animal at risk. The morphometries of the hedgehog genera has been carried out with little attention to the comparison between its external and internal body parts. This study is therefore aim ed a t determining the relationships among the external and internal morphometries of A. aibiventris in Ibadan, Oyo State, Nigeria. Twelve (12) adult individuals comprising of 5 males and 7 females were used in this study and were all gotten from the wild in Ibadan, Nigeria. Live weights, external body measurements and weights of some internal organs were measured. Means and standard deviations were calculated. The T-tests and Pearson's correlation coefficients were conducted at a0.o5. The snout length and the tail thickness in males were significantly greater than that of females. Live weights in male correlates significantly with the trunk circumference, while in females it correlates with trunk circumference, body length, lung weight and heart weight. Several significant correlations were established among both external and internal parameters measured. This study revealed a reduction in the size of Atelerix aibiventris when compared with the previous similar studies. Factors such as increased hunting and habitat destruction might have been responsible for this.